Integrated anti-hyperlipidemic bioactivity of whole Citrus grandis [L.] osbeck fruits—multi-action mechanism evidenced using animal and cell models. Issue 4 (1st April 2020) - Lin, Li-Yun; Huang, Boa-Chan; Chen, Kuan-Chou; Peng, Robert Y.
Abstract : Multi- antihyperlipidemic mechanism revealed by the pomelo phytonutrients . Both the sterol synthesis and lipogenesis pathways are affected by the pomelo phytonutrients. Dotted line: from citation. Solid line: verified in this experiment. Abstract : Changes in human life style have increased the incidence of obesity which has become a risk factor to human health. In Taiwan, the annual production of Citrus grandis [L.] reaches 75 000 tons, while the amount of waste fruits could reach 5%. We propose that abundant phytochemicals present in the wastes can be beneficial to attenuate obesity with hyperlipidemia. An animal Wistar rat model showed that pomelo flesh, peels, carpel (the segmental membrane), as well as the essential oil attenuated obesity as well as hyperlipidemia, and the AMPK–SREBP–PPARS pathway was involved. To further verify the mechanism, a HepG2 cell model was used to test some representative pomelo phytonutrients including limonene (Ln), γ-terpinene (γT), p -synephrine (SP), β-sitosterol (βS), and hesperidin (Hn). Data interestingly revealed it to be a multiple mechanism of anti-lipogenic bioactivity via downregulating the enzymes involved in both the cholesterol and triacylglyceride de novo biosynthesis (in the order of decreasing bioactivity): acetyl CoA carboxylase (Hn, SP, βS, Ln = γT), fatty acid synthase (Ln, γT, SP, βS, Hn), HMG-CoA synthase (Ln, Hn, SP, βS, γT), and HMG-CoA reductase (Hn, Ln, βS, γT, SP), and via upregulation of cholesterol-7α-monooxygenase (CYP7A1) (Hn, βS). In addition, all pomelo fruit parts enhanced the fecal crude lipid and sterol excretion capability. Thus, fruits of C. grandis can serve as a rather promising integrative antihyperlipidemic agent.